Identifying A User Interface Web Design Standard for Higher Learning Institutions Using Kansei Engineering - Punitha Turumugon; Aslina Baharum (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
User interface design plays an important role in web design. Designing a user interface that satisfies the emotional needs of the users is essential as the user interface plays a crucial role in generating remarkable user experiences for websites. A poorly designed user interface leads to bad user interaction while raising the users’ arousal and a displeasing user experience with a website elicits dissatisfaction emotion where consecutively results in avoidance and prevents revisit to the website. A standard emotional based user interface web design would enhance user experience which will lead to success of a website. Kansei engineering which is a popular technique in transforming users’ feelings into product design is used in this research. This study tries to convert the feelings and emotions of users into design elements with the use of Kansei engineering technology in order to design an appropriate higher learning institution website by  identifying a standard web design that cultivates emotional engagement. A standard user interface web design guideline for the development of the higher learning institutions’ website has been proposed in this research.